O MERCADO DE TRABALHO PARA O PROFISSIONAL DA HOTELARIA NAS CIDADES DE GUARULHOS E SÃO BERNARDO DO CAMPO - Ferreira, Silvia Aparecida Raimundo (2009)
This work shows that the cities Guarulhos and Sao Bernardo do Campo have tourist potential for business because there are industrial parks that allow the entry and stay of persons coming to the cities to carry out various types of business. Thus, they need to lodge, usually for a period of time where they intend to rest, feed themselves; bathe themselves as if they were in their homes. Beyond this potential, the cities have some more features in common as the location of airports, Cumbica and Congonhas, well ahead of its centers, and also serve as a transition to other cities considered more welcoming as Santos, Guaruja and others on the coast and São Paulo, the region known as the great Sao Paulo. So Guarulhos and São Bernardo end up being little used in relation to potential tourists. This study shows if to exist investments in that sector, tourism will can grow making them receptive cities to those that visit them because of work and in need of proper housing and often a place to use as your own office. With that, increases the need for qualified professionals to meet the expectations of tourists. Therefore it expands the labor market in the areas devoted to tourism and hospitality of the cities. Among them, there are Transport, Trade, Security, Food, Culture, Sports and Leisure, hotel chains and even Technical Schools and Colleges. To achieve what is proposed, it was used for primary data derived from personal interviews with some professionals linked to the sector, beyond the secondary data and information collected in the sites of the city, trade unions, means of lodging and other associations that are part of the literature it was possible to conclude that the two cities studied have tourist potential for business and may extend the labor market hotel from the awareness of stakeholders to invest in infrastructure, in training human resources, in the structure of the hotel business and the dissemination of the site, products and services offered.(AU)